A Brief Overview on Black Triangle with Its Management - Ikbal, S. K. Aziz; Siddiqui, Zeba Rahman (Research Developments in Medicine and Medical Science Vol. 2, 2023)
Along with functional periodontal health, esthetic demand is increasing among patients. Creating a perfect smile through periodontal plastic procedures or multidisciplinary approaches involving orthodontic, restorative, and prosthetic specialties is a real challenge in esthetic dentistry. “Black triangle” is one of the common causes that can compromise esthetic. Black triangle is open gingival embrasure cervical to interproximal contact. Its presence may also cause problem in phonetic and retention of food debris. This article discusses the definition, causes, classification, prevalence, and various approaches in handling the case of black triangle.